FACTORS AFFECTING COMMUNITY INTEREST IN SHARIA BANK SAVING PRODUCTS (Studies on the Community of South Tangerang City) - Intan Lilis Sugiarti; Erika Amelia; Ade Ananto Terminanto (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2020)
This research was conducted to find factors that influence people's preferences on Islamic bank savings products. This study uses primary data in the form of a questionnaire distributed to the people of South Tangerang. They have been or have been a sharia bank savings customer. This study obtained a sample of 133 respondents. To analyze this study, researchers used a factor analysis test and Chi-Square (X2) test using SPSS version 24. The factor analysis test results from this study indicate that nine factors can influence people's preferences on Islamic bank savings products. Factors formed successively include guarantee and equality of profit-sharing results, product feature factors, product quality factors, profit-sharing distribution factors, environmental factors, sharia understanding factors, sharia mechanism factors, usability factors, and shariah compliance factors. The chi-square test analysis showed that the characteristics of respondents in the form of gender, age, occupation, last education, and address have a relationship with nine factors formed.